Online music therapy during a pandemic - Górska, Edyta (Virtualizing the lives of people with disabilities, 2021)
In March 2020, because of the pandemic and lockdown, therapeutic activities for people with intellectual disabilities were suspended via revocation throughout Poland. Online music therapy became a necessity when switching to a remote form of music therapy for people with disabilities. It has become a challenge for both the leaders and the mentees. Online music therapy has turned into a daily ritual. The main research problem is the idea of conducting online music therapy. In the process of changing stationary music therapy to online music therapy, I applied innovations that have now become established as new methods. The participants were adults and children with intellectual disabilities from the PSONI center in the Pomeranian Voivodeship. This activity required the development of unconventional solutions, new methods and music therapy activities and it became one of the therapeutic measures in the period of isolation. Online music therapy has proven to be an effective method of therapy, which can successfully replace stationary music therapy in a situation of higher necessity, such as a pandemic.